(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Chronic recurrent aphthous stomatitis (CRAS) is a common oral condition marked by periodic ulcerations, discomfort of varying intensity, and unpredictable healing durations. Clinical assessment reveals inconsistencies in the local immune system, such as altered lysozyme activity and deviations in immunoglobulin content within the saliva. Microbial studies identify diverse populations of aerobic and anaerobic organisms inhabiting ulcerated areas, potentially driving ongoing inflammation and secondary infections. Laboratory evaluations suggest that weakened mucosal immunity plays a role in the persistence and depth of tissue involvement. These findings emphasize the relevance of combining clinical, immunologic, and microbial data to develop more effective, personalized treatment strategies